2019
DOI: 10.1530/eje-18-0749
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a clinicopathological score for the prediction of post-surgical evolution of pituitary adenoma: retrospective analysis on 566 patients from a tertiary care centre

Abstract: Objective and design: A clinicopathological score has been proposed by Trouillas et al. to predict the evolution of pituitary adenomas. Aim of our study was to perform an independent external validation of this score and identify other potential predictor of post-surgical outcome. Methods: The study sample included 566 patients with pituitary adenomas, specifically 253 FSH/LH-secreting, 147 GH-secreting, 85 PRL-secreting, 72 ACTH-secreting and 9 TSH-secreting tumours with at least 3-year post-surgical follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 23 publications
1
72
0
Order By: Relevance
“…Despite improvements, the WHO classification still lacks significant prognostic impact. Recent retrospective and prospective studies on large number of patients operated on for pituitary neuroendocrine tumours have demonstrated that combined use of proliferative markers and tumour invasion as a five‐tiered score strongly predicts persistent tumour disease and early progression/recurrence after surgery . Based on the published studies, it is to be expected that inclusion of both cell proliferation and tumour invasion, as previously proposed , in combination with the definition of potentially aggressive histological subtypes, would significantly improve prognostic and predictive value of the WHO classification of pituitary neuroendocrine tumours.…”
Section: Future Perspectives and Research Agenda In The Field Of Pathmentioning
confidence: 95%
“…Despite improvements, the WHO classification still lacks significant prognostic impact. Recent retrospective and prospective studies on large number of patients operated on for pituitary neuroendocrine tumours have demonstrated that combined use of proliferative markers and tumour invasion as a five‐tiered score strongly predicts persistent tumour disease and early progression/recurrence after surgery . Based on the published studies, it is to be expected that inclusion of both cell proliferation and tumour invasion, as previously proposed , in combination with the definition of potentially aggressive histological subtypes, would significantly improve prognostic and predictive value of the WHO classification of pituitary neuroendocrine tumours.…”
Section: Future Perspectives and Research Agenda In The Field Of Pathmentioning
confidence: 95%
“…Surgical observations have the fundamental role of providing data for diagnosis of extension or invasion of PAs [7,[58][59][60][61].…”
Section: Pas and Surgical Invasivenessmentioning
confidence: 99%
“…To overcome these limits, a grading system based on the combination of clinical and histopathological features, which correlates with high accuracy with the clinical outcome in term of recurrence rate and disease persistence, has been recently proposed by Trouillas et al [137]. This system has been validated in independent reports [61,138] and included as integrated diagnostic information within the algorithm proposed for a standardized diagnostic approach to PitNETs by the European Pituitary Pathology Group (EPPG) [139]. The proposed grading system is basically founded on three major tumor features related to tumor size, proliferation, and invasiveness, while expression of p53, previously adopted as a potential marker of PitNET aggressiveness, has been confined to a minor role, since the low frequency of p53 detection by immunohistochemistry indicates that it is inadequate as a routine marker of invasiveness.…”
Section: Pathological and Molecular Considerationsmentioning
confidence: 99%
“…The overall grade is determined by whether the tumours are invasive (1 or 2) and/or proliferative (a or b). The combination of both invasion and proliferation (grade 2b) strongly predicts recurrence or progression (Asioli et al 2019).…”
Section: Case Selection: When In the Clinical Pathway Should Temozolomentioning
confidence: 99%